Ile twarzy ma Gomorra? (Trans)medialna historia jednej książki - Korzeniecka, Weronika (Zagadnienia Rodzajów Literackich, 2020)
The aim of the article is to present Gomorra by Roberto Saviano as the largest contemporary transmedia project in Italy, which includes theatre play, movie, drama series and many other satellite works. In particular, the paper shows how the book fits into the concept of convergence culture by Henry Jenkins. The article provides answers to questions about fandom of Gomorra, about specific realizations of some of Saviano’s stories, about the nature of the relation between grassroots fan culture and creators of official productions and about the role of the writer himself in all these processes.